The Role of a 10-Week Mindfulness-Based Cognitive Behavioral Therapy Intervention in Managing Depression, Anxiety, and Stress Among the Elderly: A Quasi-Experimental Study - Garg, Rachna; Awasthi, Shubhagata; Gupta, Naveen (Journal of Neonatal Surgery, 2025)
This study investigates the effectiveness of a 10-week Mindfulness-Based Cognitive Behavioral Therapy (MBCBT) intervention in reducing symptoms of depression, anxiety, and stress among elderly individuals. Psychological distress is increasingly prevalent in older adults, yet non-pharmacological interventions remain underutilized in geriatric care. Employing a quasi-experimental pre-post design, the study was conducted with a purposive sample of 55 elderly participants aged between 60 and 75 years, selected based on their scores on the Depression Anxiety Stress Scale-21 (DASS-21). The participants were categorized into three groups according to their dominant psychological concern—depression, anxiety, or stress. Each group underwent a structured 10-week MBCBT program combining mindfulness techniques and cognitive-behavioral strategies tailored to the needs of older adults. Post-intervention analysis revealed a significant reduction in DASS-21 scores across all three groups, indicating improved emotional regulation and mental well-being. The findings support the integration of MBCBT into community mental health programs for the elderly, offering a promising alternative to medication-based treatment.